Pushing the limits of pancreatic surgery; the quest for R0 resection through mesenteric principle and evolving vascular strategies - Khatiwada, Sagar; Thakur, Binay; Tiwari, Manoj; Bhattarai, Shachee; Adhikari, Mahesh Mani; Sapkota, Sandeep; Rawat, Saujan (Nepalese Journal of Cancer, 2026)
Background: Local recurrence is a major factor contributing to poor prognosis in pancreatic carcinoma, often driven by perineural invasion in the retro-pancreatic region. To improve R0 resection rates, surgical strategies have evolved toward more radical techniques, including total mesopancreatic excision, “triangle surgery,” and routine consideration of vascular resection and reconstruction. Objective: This review aims to elucidate the anatomical basis of mesopancreatic excision and to outline a comprehensive approach for incorporating vascular strategies into pancreatic cancer surgery, ensuring a balance between oncologic radicality and perioperative safety. Methods: An extensive review of current anatomical data, recent clinical literature, and institutional surgical experience was performed. The analysis focuses on the role of the three fusion fascias (Treitz, Fredet, and Toldt), the concept of the mesopancreatic triangle, and the application of triangle surgery for complete mesopancreatic excision. It also examines the evolution of vascular resection and reconstruction from a previous contraindication to an essential component of modern oncologic surgery. Results: Total mesopancreatic excision was found to be effective in removing retroperitoneal tissue containing potential microscopic disease. The planned use of vascular resection and reconstruction, supported by improved perioperative care, is now considered crucial in patients with venous or arterial involvement. Proper understanding and handling of fusion fascias during kocherization are vital to prevent tumor exposure, maintain oncologic planes, and define clear dissection boundaries. Advances in technique have also refined indications and execution of vascular reconstruction. Conclusion: Expanding the limits of resectability in pancreatic cancer requires a shift from conventional methods to advanced mesopancreatic and vascular approaches. By integrating evidence-based knowledge with practical surgical expertise, this review offers a structured guide for residents and surgeons to manage the complexities of pancreatic oncology and achieve optimal R0 resection outcomes.